Cardinal's The Words to Say it: The Words to Reproduce Mother - Eilene Hoft-March (Studies in 20th & 21st Century Literature, 1997)
The Words to Say it, an autobiographical novel by Algerian-born Frenchwoman Marie Cardinal, earned praise for the accuracy with which it documents a classic psychoanalysis. Quickly sketched, the plot seems to suggest that the separation from an overpowering mother is effected by paternal language and phallic law—the normal, normative psychic itinerary of the human subject. In its reconsideration of the Oedipal, this essay explores Irigaray's idea of the ambiguities of separation from mother and the possibility that the story of (feminine) subjectivity begins with the mother, begins with affiliation and affirmation even as it speaks of separateness. From this perspective, the protagonist's cure comes about when she associates with her mother's belated madness and sees it as a revolt against the phallic laws of their bourgeois class and against the colonial laws of their Algerian homeland. In the last stages of analysis, the protagonist remembers the language her mother taught her to evoke all the particularities of Algeria; this maternal tongue connects the protagonist both to mother and Motherland. The image of a nurturing Algeria calls for a re-analysis of the cultural drama of the unnamed Algerian war. If the book models an investigation of other psychic versions that challenge what otherwise might be too readily assumed as psychoanalytic law, the book also suggests re-articulating what otherwise might be too readily assumed as cultural law and order.
Keywords: The Words to Say it; autobiography; novel; Marie Cardinal; psychoanalysis; mother; mother figure; phallic law; feminine subjectivity; bourgeois; cultural law